Which professional skills do students learn in engineering team-based projects?. (4th March 2022) - Picard, Cyril; Hardebolle, Cécile; Tormey, Roland; Schiffmann, Jürg
ABSTRACT: Engineering accreditation bodies express a strong consensus that in addition to technical and scientific skills, engineering education also needs to promote the development of professional skills. In general, team-based projects are considered to be valuable approaches to develop such skills and have been extensively added to engineering curricula. Yet, it remains unclear which skills and to what extent students learn from these interventions. The challenge of assessing the development of those skills is an important factor in this gap. In this paper, we used a standardised self-reporting questionnaire to evaluate the development of students' self-efficacy beliefs through in-course and capstone projects. Results suggest that students only marginally develop these skills when they are not explicitly addressed as part of the project, showing ways to more effectively support student learning of professional skills. The questionnaire also proved to be an effective and scalable way to assess large classes.